The Relationship of Pharmaceutical Service Quality with Outpatient Satisfaction in Internal Medicine Polyclinic - Indra Ginting; Asriwati Asriwati; Artha Putri Napitupulu (Newinera Publisher, 2021)
It is a direct and responsible service to patients in the pharmaceutical field, which aims to enhance the quality of life of patients by attaining certain goals. Satisfaction is a result of how people perceive their own and others' performances. The performance of the health services received by new patients will be pleased if it meets or surpasses their expectations, and patient disappointment or discontent will develop if the performance of the health services received does not meet their expectations. The purpose of this research was to find out whether there was a link between patient satisfaction at H. Adam Malik Hospital and the quality of the pharmaceutical services provided. Researchers at Medan's Haji Adam Malik Hospital used cross-sectional survey analysis to examine the link between the independent and dependent variables, namely, the quality of pharmaceutical services provided and patient satisfaction. Aromatherapy wind oil preparations using small white ginger essential oil (Zingiber officinale Roscoe) concentrations of 4%, 5%, and 6% meet the criteria, the organoleptic test is a light yellow, clear liquid, had a distinctive smell and felt warm, homogeneity, the wind oil pH test is 6, the irritation test was non-existent, and the hedonic test was successful. Outpatient satisfaction with pharmaceutical services at H. Adam Malik Hospital Medan was shown to be associated with the quality of pharmaceutical services, according to the study's findings.